Biosynthesis of gold and silver nanoparticles using emblica officinalis fruit extract, their phase transfer and transmetallation in an organic solution - Ankamwar, Balaprasad; Damle, C.; Ahmad, Absar; Sastry, M. (Journal of Nanoscience and Nanotechnology, 2005)
The design, synthesis and characterization of biologically synthesized nanomaterials have become an area of significant interest. In this paper, we report the extracellular synthesis of gold and silver nanoparticles using Emblica Officinalis (amla, Indian Gooseberry) fruit extract as the reducing agent to synthesize Ag and Au nanoparticles, their subsequent phase transfer to an organic solution and the transmetallation reaction of hydrophobized silver nanoparticles with hydrophobized chloroaurate ions. On treating aqueous silver sulfate and chloroauric acid solutions with Emblica Officinalis fruit extract, rapid reduction of the silver and chloroaurate ions is observed leading to the formation of highly stable silver and gold nanoparticles in solution. Transmission Electron Microscopy analysis of the silver and gold nanoparticles indicated that they ranged in size from 10 to 20 nm and 15 to 25 nm respectively. Ag and Au nanoparticles thus synthesized were then phase transferred into an organic solution using a cationic surfactant octadecylamine. Transmetallation reaction between hydrophobized silver nanoparticles and hydrophobized chloroaurate ions in chloroform resulted in the formation of gold nanoparticles.
Keywords: Biosynthesis; Nanomaterials; Phase transfer; Transmetallation

Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Extra-/intracellular biosynthesis of gold nanoparticles by an alkalotolerant fungus, trichothecium sp. - Ahmad, Absar; Senapati, Satyajyoti; Khan, Mohammad Islam; Kumar, Rajiv; Sastry, Murali (Journal of Biomedical Nanotechnology, 2005)
The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. As part of our ongoing investigation into the use of fungi for nanoparticle synthesis, we report herein that depending on the reaction conditions of the fungus Trichothecium sp. with aqueous gold ions, gold nanoparticle synthesis can be controlled to occur either within the biomass or extracellularly. Moreover, we have found that reaction of gold ions with the Trichothecium sp. fungal biomass under stationary conditions results in the rapid extracellular formation of gold nanoparticles of spherical, rod-like and triangular morphology whereas reaction of the biomass under shaking conditions resulted in intracellular growth of the nanoparticles. It is believed that on changing the reaction conditions of the fungus with gold ions, the enzymes and proteins which are being released into the medium under stationary conditions do not get released under shaking conditions resulting in the formation of extracellular or intracellular gold nanoparticles respectively. The gold nanoparticles are not toxic to the cells and the cells continued to grow after the biosynthesis of the gold nanoparticles in both the cases.
Keywords: Biosynthesis; enzymes; Fungus; Gold; Morphology Control; Nanoparticles

Gold nanotriangles biologically synthesized using tamarind leaf extract and potential application in vapor sensing - Ankamwar, Balaprasad; Chaudhary, M; Sastry, M (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2005)
The size and shape dependent electronic and chemical properties of metal nanoparticles has drawn the attention of chemists, physicists, biologists, and engineers who wish to use them for the development of new generation nanodevices. In this article, we report the synthesis of gold nanotriangles using tamarind leaf extract as the reducing agent. On treating aqueous chloroauric acid solution with tamarind leaf extract, rapid reduction of the chloroaurate ions is observed leading to the formation of flat and thin single crystalline gold nanotriangles. Atomic force microscopy analysis of the gold nanotriangles indicated that they ranged in thickness from 20 to 40 nm. These gold nanotriangles with unique and highly anisotropic planer shapes might find application in photonics, optoelectronics, and optical sensing. We investigated the effect of different organic solvent vapors like methanol, benzene and acetone on the conductivity of tamarind leaf extract reduced gold nanotriangles. I-V characteristics measurement of these nanotriangles was done in presence of these organic solvent vapors. The observed characteristics suggest the application of gold nanotriangles to future chemical sensors.
Keywords: Biosynthesis; gold nanotriangles; tamarind leaf; vapor sensing

Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles

Extracellular synthesis of crystalline silver nanoparticles and molecular evidence of silver resistance from morganella sp.: towards understanding biochemical synthesis mechanism - Parikh, Rasesh Y.; Singh, Sanjay; Bhagavatula L. V. Prasad; Patole, Milind S.; Sastry, Murali; Shouche, Yogesh S. (ChemBioChem, 2008)
There has been significant progress in the biological synthesis of nanomaterials. However, the molecular mechanism of synthesis of such bio-nanomaterials remains largely unknown. Here, we report the extracellular synthesis of crystalline silver nanoparticles (AgNPs) by using Morganella sp., and show molecular evidence I of silver resistance by elucidating the synthesis mechanism. The AgNPs were 20 +/- 5 nm in diameter and were highly stable at 1 room temperature. The kinetics of AgNPs formation was investigated. Detectable particles were formed after on hour of reaction, and their production remained exponential up to 18 h, and saturated at 24 h. Morganella sp. was found to be highly resistant to silver cations and was able to grow in the presence of more than 0.5 mm AgNO3. Three gene homologues viz. silE, silP and silS were identified in silver-resistant Morganella sp. The homologue of silE from Morganella sp. showed 99% nucleotide sequence similarity with the previously reported gene, silE, which encodes a periplasmic silver-binding protein. The homologues of silP and silS were also highly similar to previously reported sequences. Similar activity was totally absent in closely related Escherichia coli; this suggests that a unique mechanism of extracellular AgNPs synthesis is associated with silver-resistant Morganella sp. The molecular mechanism of silver resistance and its gene products might have a key role to play in the overall synthesis process of AgNPs by Morganella sp. An understanding of such biochemical mechanisms at the molecular level might help in developing an ecologically friendly and cost-effective protocol for microbial AgNPs synthesis.
Keywords: Biosynthesis; Morganella sp.; Nanoparticles; sil gene homologues; Silver

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Bacterial synthesis of phtocatalytically active and biocompatible TiO2 and ZnO nanoparticles - Singh, Sanjay; Britto, Virginia D.; Bharde, Atul A.; Sastry, Murali; Dhawan, Alok; Bhagavatula L. V. Prasad (International Journal of Green Nanotechnology: Physics and Chemistry, 2010)
TiO2 and ZnO nanoparticles are well known for their photocatalytic and ultraviolet (UV)-absorbent properties and have successfully entered into the market as consumer products. Large volume production of these nanoparticles by industries require environmentally friendly processes of synthesis. In this article, we show that when challenged with an appropriate precursor, the bacterium Actinobacter spp. can lead to the extracellular synthesis of ZnO and TiO2 nanoparticles. The biological way of synthesizing these materials probably leads to the in situ doping of elements like C, F, and N into their crystal lattices, which is evidenced by a red shift in the absorption edge. Because the doping is expected to affect the photocatalytic activity of these materials under different light conditions, such investigations have also been undertaken here. Further, the biocompatibility of these nanomaterials (cytotoxicity and genotoxicity) has also been investigated in detail.
Keywords: Biosynthesis; genotoxicity; Nanoparticles; Nanotoxicity; Photocatalysis

Vice to virtue: intracellular biogenic nanoparticles for the generation of carbon supported catalysts - Vijayakumar, P. S.; Selvakumar, S.; Gholap, Ramkrishna S.; Singh, A. P.; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2010)
Intracellular biogenic nanoparticles are considered disadvantageous as the separation of the nanoparticles from the biomass becomes intricate. However realizing the importance of carbon supported catalyst for many important organic reactions we envisaged these nanoparticles as a source for carbon supported catalyst. Herein we demonstrate the heat treatment of intracellular biogenic nanoparticles under inert atmosphere as an efficient method for the preparation of carbon supported metal oxide catalysts. Aspergillus ochraceus, a fungus isolated from foundries, on incubation with K(2)TiF(6) led to the synthesis of intracellular titanium oxide nanoparticles. The nanoparticles embedded biomass upon heat treatment at 600 degrees C in a nitrogen environment gave titanium oxide nanoparticles implanted in a carbonaceous matrix. The material thus formed was characterized using FTIR spectroscopy, Raman spectroscopy, HRTEM and X-ray diffraction. Appreciable benzaldehyde selectivity was observed when styrene oxidation was carried out over such immobilized catalysts. The conversion rate was determined to be 76% and the benzaldehyde selectivity was greater than 80%.
Keywords: Benzaldehyde Selectivity; Biosynthesis; Carbon Supported Titania; Nanoparticles; Styrene Oxidation

Synthesis of gold nanoparticles by various leaf fractions of Semecarpus anacardium L. tree - Raju, D.; Mehta, Urmil J.; Hazra, Sulekha (Trees-Structure and Function, 2011)
Gold nanoparticles (NPs) were synthesized using Semecarpus anacardium leaf extracts in water and the green biomass. Extract prepared at ambient condition by crushing the leaves in deionized water is identified as `green extract', and that by boiling the leaf pieces as `boiled extract'. The mass remaining after separating the `green extract' is identified as `green biomass'. These components triggered rapid reduction of Au(III) to Au (0) in HAuCl4 solution indicating the natural ability of the leaves of S. anacardium to synthesize NPs in ambient conditions. Green extract produced more NPs compared to the boiled extract suggesting denaturization of some of the useful factors due to boiling. NPs were quantified using UV and ICP-AES analysis. These were characterized using Transmission electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction. TEM images of the particles formed with green extract, boiled extract and green biomass showed that the particles were of different shapes and sizes.
Keywords: Biosynthesis; gold nanoparticles; Green extract; Semecarpus; TEM

Extracellular biosynthesis of platinum nanoparticles using the fungus fusarium oxysporum - Syed, Asad; Ahmad, Absar (Colloids and Surfaces B-Biointerfaces, 2012)
Nanoscience is a blooming field and promises a better future. In order to fabricate nanoparticles in an eco-friendly and inexpensive manner, significant efforts are being made to replace the chemical and physical methods currently being used with the biological methods. Chemical methods are toxic while the physical ones are very expensive. Biological methods, apart from being cost-effective, also provide protein capped nanoparticles which are thus very stable, have good dispersity and do not flocculate, and may find use in various applications. The present work emphasizes on platinum nanoparticles synthesis protocol which occurs at ambient conditions. The fungus Fusarium oxysporum when incubated with hexachloroplatinic acid (H2PtCl6) in ambient conditions reduces the precursor and leads to the formation of stable extracellular platinum nanoparticles. The biosynthesis of platinum nanoparticles was monitored by UV-visible spectroscopy and these nanoparticles were completely characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The nanoparticles are in the size range of 5-30 nm and are stabilized by proteins present in the solution. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, fungal-based method for the synthesis of nanoparticles over a wide range of chemical compositions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Fungus; Nanoparticles; platinum

Intracellular synthesis of gold nanoparticles using alga tetraselmis kochinensis - Senapati, Satyajyoti; Syed, Asad; Moeez, Sana; Kumar, Ashutosh; Ahmad, Absar (Materials Letters, 2012)
The development of eco-friendly synthesis protocol for the synthesis of nanoscale materials of different compositions, shapes and sizes is an important area of research in the field of nanotechnology. In this paper, we report on the use of alga Tetraselmis kochinensis in the intracellular synthesis of gold nanoparticles of dimensions 5-35 nm. The particles are more concentrated upon the cell wall than on the cytoplasmic membrane, possibly due to reduction of the metal ions by enzymes present in the cell wall and cytoplasmic membrane. These intracellular nanoparticles may have applications in drug delivery, biomedical applications, catalysis, etc. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Algae; Biosynthesis; Nanoparticles; nanotechnology; Tetraselmis kochinensis

Extra- and intracellular gold nanoparticles synthesis using live peanut callus cells - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Current Nanoscience, 2013)
An important challenge of considerable topical significance in nanotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials in large quantities with variable sizes, shapes and chemical compositions. Green synthesis routes for the production of inorganic metal nanoparticles using whole cell of microorganisms and plant extracts are gaining tremendous popularity as these are non-toxic, cheap and occur at ambient conditions. The present work emphasizes on gold nanoparticles synthesis protocol using live plant callus cells. Peanut callus cells when incubated with HAuCl4 solution in ambient conditions reduced the precursor and lead to formation of well dispersed, water soluble extracellular and intracellular gold nanoparticles within 24 hours. The biosynthesis of gold nanoparticles was monitored by UV-visible spectroscopy (UV-Vis) and further characterized by X-ray diffraction analysis (XRD), Energy Dispersive Spectroscopy (EDS) and Selected Area Electron Diffraction (SAED). The particle size distribution shows that the average particle size is 50 nm for extra-and 31 nm for intracellular gold nanoparticles. The nanoparticles may be stabilized by proteins secreted by callus cells. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, plant cell-based method for the synthesis of nanoparticles over a wide range of chemical compositions.
Keywords: Biosynthesis; callus; gold nanoparticles; live cells; Peanut; TEM

Extracellular biosynthesis of CdTe quantum dots by the fungus fusarium oxysporum and their anti-bacterial activity - Syed, Asad; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
The growing demand for semiconductor [quantum dots (Q-dots)] nanoparticles has fuelled significant research in developing strategies for their synthesis and characterization. They are extensively investigated by the chemical route; on the other hand, use of microbial sources for biosynthesis witnessed the highly stable, water dispersible nanoparticles formation. Here we report, for the first time, an efficient fungal-mediated synthesis of highly fluorescent CdTe quantum dots at ambient conditions by the fungus Fusarium oxysporum when reacted with a mixture of CdCl2 and TeCl4. Characterization of these biosynthesized nanoparticles was carried out by different techniques such as Ultraviolet-visible (UV-Vis) spectroscopy, Photoluminescence (PL), X-ray Diffraction (XRD), X-ray Photoelectron spectroscopy (XPS), Transmission Electron Microscopy (TEM) and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. CdTe nanoparticles shows antibacterial activity against Gram positive and Gram negative bacteria. The fungal based fabrication provides an economical, green chemistry approach for production of highly fluorescent CdTe quantum dots. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Biosynthesis; CdTe; Fungus; Nanoparticles

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles

Biosynthesis of silver nanoparticles by using ganoderma-mushroom extract - Ekar, S. U.; Khollam, Y. B.; Koinkar, Pankaj M.; Mirji, S. A.; Mane, R. S.; Naushad, M.; Jadhav, S. S. (Modern Physics Letters B, 2015)
Present study reports the biochemical synthesis of silver nanoparticles (Ag-NPs) from aqueous medium by using the extract of medicinal mushroom Ganoderma, as a reducing and stabilizing agents. The Ag-NPs are prepared at room temperature by the reduction of Ag+ to Ag in aqueous solution of AgNO3. The resultant particles are characterized by using UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy and transmission electron microscopy (TEM) measurement techniques. The formation of Ag-NPs is confirmed by recording the UV-visible absorption spectra for surface plasmon resonance (SPR) where peak around 427 nm. The prominent changes observed in FTIR spectra supported the reduction of Ag+ to Ag. The morphological features of Ag-NPs are evaluated from HRTEM. The spherical Ag-NPs are observed in transmission electron microscopy (TEM) studies. The particle size distribution is found to be nearly uniform with average particle size of 2 nm. The Ag-NPs aged for 15, 30, 60 and 120 days showed no profound effect on the position of SPR peak in UV-visible studies, indicating the protecting/capping ability of medicinal mushroom Ganoderma in the synthesis of AgNPs.
Keywords: Biosynthesis; Ganoderma; medicinal mushroom; silver nanoparticles; UV-visible spectroscopy

Biogenic terbium oxide nanoparticles as the vanguard against osteosarcoma - Iram, Sana; Khan, Salman; Ansary, Abu Ayoobul; Arshad, Mohd; Siddiqui, Sahabjada; Ahmad, Ejaz; Khan, Rizwan H.; Khan, Mohd Sajid (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2016)
The synthesis of inner transition metal nanoparticles via an ecofriendly route is quite difficult. This study, for the first time, reports synthesis of terbium oxide nanoparticles using fungus, Fusarium oxysporum. The biocompatible terbium oxide nanoparticles (Tb2O3 NPs) were synthesized by incubating Tb4O7 with the biomass of fungus F. oxysporum. Multiple physical characterization techniques, such as UV-visible and photoluminescence spectroscopy, TEM, SAED, and zeta-potential were used to confirm the synthesis, purity, optical and surface characteristics, crystallinity, size, shape, distribution, and stability of the nanoemulsion of Tb2O3 NPs. The Tb2O3 NPs were found to inhibit the propagation of MG-63 and Saos-2 cell-lines (IC50 value of 0.102 mu g/mL) and remained non-toxic up to a concentration of 0373 gg/mL toward primary osteoblasts. Cell viability decreased in a concentration-dependent manner upon exposure to 10 nmTb(2)O(3) NPs in the concentration range 0.023-0373 mu g/mL Cell toxicity was evaluated by observing changes in cell morphology, cell viability, oxidative stress parameters, and FACS analysis. Morphological examinations of cells revealed cell shrinkage, nuclear condensation, and formation of apoptotic bodies. The level of ROS within the cells an indicator of oxidative stress was significantly increased. The induction of apoptosis at concentrations <= IC50 was corroborated by 4',6-diamidino-2-phenylindole dihydrochloride (DAPI) staining (DNA damage and nuclear fragmentation). Flow-cytometric studies indicated that the response was dose dependent with a threshold effect. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Cytotoxicity; fusarium oxysporum; Osteosarcoma; Tb2O3 nanoparticles

Phenol oxidative dearomatization of modified nucleoside templates: a simple access to the c7-spiroannulated octosyl acid framework - Mullapudi, Venkannababu; Bhogade, Ravindra B.; Deshpande, Mukund V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2017)
Phenol oxidative dearomatization and cyclization has been executed successfully on nucleoside templates to synthesize C7-spiroannulated perhydrofuropyran nucleosides and C6-spiroannulated perhydrofurofuran nucleosides as novel analogues of octosyl acid and related peptidyl nucleosides.
Keywords: Analogs; antibiotics; Biosynthesis; Chitin synthase; Derivatives; Ezomycins; Glucose Diacetonide Natural-products; Griseofulvin; Malayamycin; Modified nucleosides; Moiety; Peptidyl Glycosides; Phenol Oxidative Dearomatization; Vorbruggen Glycosylation

Alpha Au2S nanoparticles: fungal-mediated synthesis, structural characterization and bioassay - Syed, Asad; Al Saedi, Marzouq H.; Bahkali, Ali H.; Elgorgan, Abdallah M.; Kharat, Mahesh; Pai, Kalpana; Pichtel, John; Ahmad, Absar (Green Chemistry Letters and Reviews, 2022)
Luminescent nanoparticles synthesized via bio-based protocols that generate nanoparticles having different chemical compositions along with other functionalities (size and morphology) have received huge attention. We have focused our research on gold sulfide nanoparticles (Au2S NPs) and have biosynthesized these NPs using the fungus Humicola sp. The nanoparticles were characterized by Transmission Electron Microscopy, which showed spherical morphology of Au2S. UV-Visible-NIR spectrophotometry, luminescence spectrophotometry, Selected Area Electron Diffraction, Energy Dispersive Analysis of X-rays, and X-ray diffraction were performed. FTIR confirmed that the fungal metabolites including biomolecules secreted in the reaction medium are primarily responsible for nanoparticle synthesis and stabilization. The fungus reduced the precursor solution (HAuCl4 and Na2SO3) and at the same time capped them with secreted biomolecules. The anti-leishmanial activity of Au2S NPs was determined against L. donovani promastigote (Ag83 strain). Au2S NPs displayed less cytotoxicity towards both normal and cancer (Daudi, ZR-75-1) cell lines. Hemocompatibility was determined via hemolysis assays. This novel fungal-based system demonstrates an economical and environmentally benign process for biosynthesis of Au2S nanoparticles which may find application in bioimaging and labeling studies.
Keywords: Biosynthesis; Cytotoxicity; Gold sulfide; Hemolysis; humicola sp; promastigote